EVALUASI PELAKSANAAN LAYANAN BIMBINGAN BELAJAR OLEH GURU DI SEKOLAH DASAR - Andriani, Miranti Widi (Jurnal Ilmiah Mandala Education (JIME), 2022)
The presence of tutoring in schools is very important in helping learners adjust themselves to academic, social, and workplace demands. Learning problems often bring inequality both socially and psychologically. The purpose of this study is to find the gaps that occur between the standards of the provision of guidance services to learn the factual conditions of the provision of tutoring services in primary schools by teachers as guidance and counselors. This research uses evaluation approach and procedure in evaluation activity of school counseling service that is using discrepancy model (gap model). The discrepancies model describes the gap between the standard (defined standard) in the counseling program and the actual performance of the school counseling program. Some research findings There is still a gap between the actual performance of teachers in providing learning guidance services with the standard performance of provision of guidance services that have been determined. There is still a gap between the actual process of implementation of the guidance services of learning with the standard process of implementation of guidance services that have been determined